Promulgation, condescension, porosity and defence: the relationship between Saint-Simonianism and Owenism (1816–1834). Issue 2 (17th February 2021) - Bellet, Michel
ABSTRACT: This article aims to add an important new dimension to the historical scholarship on early socialism by analysing the Saint-Simonian encounter with Owenism during the first decades of the nineteenth century. The article shows how the Saint-Simonian interpretation of Owenism was shaped by the manner by which the Saint-Simonians disseminated their doctrine. It draws on a number of neglected texts to show what the Saint-Simonians drew from Owen's work and how they set out to distinguish themselves from Owen and his French followers. The article focuses on key Saint-Simonian publications, including Le Globe and those edited by women members of the movement, Jeanne-Désirée Veret and Marie-Reine Guindorf's La Tribune des femmes, and its early iterations. The article shows in detail the extent to which the Saint-Simonians saw Owen's work as threatening to their cause, and how they formulated a thoroughgoing critique of it.